Effects of Probiotics on Growth and Production of Monosex Tilapia (Oreochromis Niloticus) in Nylon Net Cages at Dekar Haor, Sunamganj, Bangladesh - Das, P; Islam, MS; Biswas, M; Das, PR; Arif, ASM (Journal of the Asiatic Society of Bangladesh, Science, 2018)
To assess the effect of probiotics on growth, survival rate and production performance of all monosex tilapia (Oreochromis niloticus) for a period of 120 days in 2016 in nylon net cages placed in Dekar haor of Sunamganj district. The study was categorized into four treatments as T1 (brand a), T2 (brand b), T3 (brand c) and T4 (control) based on probiotics and each having three replicates. Cages were stocked with nursed male tilapia fry at a density of 35 nos./m3 with average size of 14.33 ± 6.41 - 16.33 ± 3.15 g. Tilapia of all the cages were fed with commercial mega floating feed at a decreasing rate of 10 - 5% of total biomass thrice daily. Feed was supplemented with probiotics at a rate of 0.5 g/kg. Comparatively higher growth (307.33 ± 33.92 g), survival rate (97.6 ± 4.90%), yield (10.5 ± 1.15 kg/m3), net profit (Tk.798.96 ± 90.85/m3) and lower food conversion ratio (1.16) were secured in T3 than that of other treatments, which were manifolds higher than the earthen freshwater and brackish waterbodies. Therefore, results of the study reveal that probiotics may be used in aquaculture for increasing fish production. Asiat. Soc. Bangladesh, Sci. 44(1): 69-78, June 2018